2014
DOI: 10.3390/ijms15010927
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Radiation on the Immune Response to Cancers

Abstract: In cancer patients undergoing radiation therapy, the beneficial effects of radiation can extend beyond direct cytotoxicity to tumor cells. Delivery of localized radiation to tumors often leads to systemic responses at distant sites, a phenomenon known as the abscopal effect which has been attributed to the induction and enhancement of the endogenous anti-tumor innate and adaptive immune response. The mechanisms surrounding the abscopal effect are diverse and include trafficking of lymphocytes into the tumor mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
168
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(174 citation statements)
references
References 71 publications
(80 reference statements)
3
168
0
3
Order By: Relevance
“…Deficiency of immune-related molecules or cells dampens the efficacy of conventional tumor therapy (23,25). Studies have shown that in successful tumor treatments, including radiation therapy (3,23,26,27), hyperthermia therapy (4) and chemotherapy (5, 28 -30), endogenous anti-tumor immunity is elicited and is demonstrably effective. Recently, the success of PD-1 and PD-L1 antibodies in combating tumors has provided support for the notion that endogenous anti-tumor immunity participates in tumor elimination (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of immune-related molecules or cells dampens the efficacy of conventional tumor therapy (23,25). Studies have shown that in successful tumor treatments, including radiation therapy (3,23,26,27), hyperthermia therapy (4) and chemotherapy (5, 28 -30), endogenous anti-tumor immunity is elicited and is demonstrably effective. Recently, the success of PD-1 and PD-L1 antibodies in combating tumors has provided support for the notion that endogenous anti-tumor immunity participates in tumor elimination (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…In cancer therapy, ionizing radiation passes through and causes damages to normal tissues, even when accurate physical techniques are applied, such as Stereotactic Radiotherapy. Radiation may also cause a shift of Th1 to Th2 immune response, and thus caused immunosuppression [6,7]. The only FDA approved radioprotector is amifostine, which is not free of toxicity [8].…”
Section: Introductionmentioning
confidence: 99%
“…IR often causes imbalance of immune response, one example of which is the shift from Th1 to Th2 response [6]. Radiation-induced Th1/Th2 imbalance also accounts for immunosuppression in irradiated animals and human [32].…”
mentioning
confidence: 99%
“…Pro-inflammatory cytokine, 29,30 promotes infiltration of leucocytes, 30,31 upregulated during hypoxia, 31 increases tumor invasiveness and angiogenesis 31 Induced after high-dose radiation 6,29 IL-1β (IL-1F2) Pro-inflammatory cytokine 22,30,32 at low doses, 33 agonistic protein to IL-1α, 30 increases tumor invasiveness and angiogenesis 31 at high doses 33 Induced after radiation 32 Induced after radiation 32,37 TNF-α (TNFSF1A) Proinflammatory cytokine, 29,32 IL-1, and TNF-α stimulate their own and each other's production 33 Induced after radiation, 29,32,37 Induced after high dose radiation 6 GM-CSF: granulocyte-macrophage colony-stimulating factor; IFN: interferon; IL: interleukin; TNF: tumor necrosis factor; NK cells: natural killer cells. the lack of both of these cytokines after RIT implicates that no such immune stimulation was initiated.…”
Section: Il-1α (Il-1f1)mentioning
confidence: 99%